A "Google Image" diagnosis of Madelung's disease. (2nd March 2015) - Mumoli, Nicola; Vitale, Josè; Sabatini, Silvia; Manni, Carolina; Masi, Lorenzo; Mazzi, Valeria; Cei, Marco; Giorgetti, Silvia; Rossi, Monica; Comassi, Mario; Camaiti, Alberto
Lesson: Given the rare nature of Madelung's disease many clinicians will not have seen a patient with it and will not be able to recognise them: subsequently a diagnosis is unlikely to be made.